Perancangan User Interface dan User Experience Pada Sistem Inventaris Menggunakan User Centered Design - Alexander, Willy; Arianto, Juli; Marfuah (Journal of Digital Ecosystem for Natural Sustainability, 2025)
With the growing influence of digital technology, the demand for a more efficient and accurate inventory system has become increasingly relevant, especially for companies that still rely on semi-manual record-keeping. This study was conducted at PT Kanindo Mandiri Sukses, where the current inventory process is still handled conventionally. Such a system often leads to difficulties in tracking data and increases the chance of input errors. To resolve these issues, this research designed a web-based inventory system tailored to user needs by applying the User Centered Design (UCD) approach. The design process involved identifying users, formulating requirements, creating a prototype interface using Figma, and evaluating the user experience through the User Experience Questionnaire (UEQ) method. The evaluation results revealed high scores in five UX aspects: Attractiveness, Perspicuity, Efficiency, Dependability, and Stimulation. The Novelty aspect scored moderately, indicating opportunities for improvement in innovation. Feedback from four internal employees indicated that the system helped simplify data entry and improved the efficiency of daily operations. It is expected that this system will support a more structured and effective inventory process in the company.